Impact of race and ethnicity on family participation in systemic lupus erythematosus genetic studies - Scofield, R Hal; Sharma, Rohan; Aberle, Teresa; Cooney, Carisa M; Kelly, Jennifer A; Harley, John B; Rasmussen, Astrid (Frontiers in Lupus, 2023)
Objective: Systemic lupus erythematosus (SLE) has a higher prevalence and is more severe in African Americans and Hispanics than in non-Hispanic Whites. To understand the shared and unique genetic risk factors of these populations, an adequate representation of African Americans and Hispanics in clinical and genetic research is indispensable while challenging. The goal of this study was to identify differences in research participation of families of different racial and ethnic backgrounds and the potential causes for the disparities. Methods: Families were screened for eligibility to the Lupus Family Registry and Repository (LFRR) after self-referral or physician referral. We recorded the sociodemographic characteristics, self-identified race and ethnicity, ACR-SLE criteria, and the reasons given for not completing study participation for all families. Results: A total of 1472 families (950 non-Hispanic White, 405 African American, and 117 Hispanic) were screened but only 366 completed study participation (25%). Participation rates and reasons for non-participation varied between racial and ethnic groups. The main reason for African American families to not participate was that subjects critical to the family structure declined participation (OR=1.6, p=0.0001), while for White families, the main cause was that purported SLE patients did not meet ACR SLE criteria (OR=1.81, p<0.00002). Hispanics were the most likely to complete participation (OR=4.25, p<0.0001). Conclusions: Successful recruitment of patients, families, and specific demographic groups is critical for the study of genetically complex diseases, such as SLE. There are significant disparities in SLE family recruitment across groups of people, likely due to their richly different cultures and environments.